ELECTRICALLY ADDRESSABLE VESICLES – TOOLS FOR DIELECTROPHORESIS METROLOGY - Desai, Salil P. (2009)
Dielectrophoresis (DEP) has emerged as an important tool for the manipulation of bioparticles ranging from the submicron to the tens of microns in size. Here we show the use of phospholipid vesicle electroformation techniques to develop a new class of test particles with specifically engineered electrical properties to enable identifiable dielectrophoretic responses in microfabricated systems. These electrically addressable vesicles (EAVs) enable the creation of electrically distinct populations of test particles for DEP. EAVs offer control of both their inner aqueous core and outer membrane properties; by encapsulating solutions of different electrolyte strength inside the vesicle and by incorporating functionalized phospholipids containing PEG brushes attached to their hydrophilic head group in the vesicle membrane, we demonstrate control of the vesicles’ electrical polarizabilities. This combined with the ability to encode information about the properties of the vesicle in its fluorescence signature, form the first steps toward the development of EAV populations as metrology tools for any DEP-based microsystem.